Physical Activity, Loneliness, and Meaning of Friendship in Young Individuals – A Mixed-Methods Investigation Prior to and During the COVID-19 Pandemic With Three Cross-Sectional Studies - Lippke, Sonia; Fischer, Marie Annika; Ratz, Tiara (Frontiers in Psychology, 2021)
Meaningful social interactions and regular physical activity are inversely associated with loneliness. Using a mixed-methods research design employing quantitative and qualitative research approaches, this research aimed to explore loneliness, physical activity, friendship, and experiences relating to the COVID-19 pandemic both prior to and during the pandemic. Quantitative data of (1) n=363 first-year university students assessed in 2018/2019 and of (2) n=175 individuals aged 18-29 years assessed in 2020 were gathered using independent self-administered online surveys. In addition, (3) n=4 students were recruited for semi-structured, qualitative interviews in 2020 during the onset phase of the COVID-19 pandemic. Correlation and regression analyses as well as analyses of variance were conducted. Thematic analysis as a qualitative method was used to explore the role physical activity, friendship, and social interactions played in loneliness, particularly in times of social isolation and social distancing. Results revealed associations of varying strength between physical activity and loneliness in 2018/2019 (r=-.09, p≤.05) and 2020 (r=-.20, p<.01). In 2020, n=73 (41.7%) participants felt that their loneliness had increased since the COVID-19 social and physical distancing guidelines were introduced, but this was not associated with a perceived change in physical activity (r=-.05, p>.05). Analyses of qualitative data revealed three main themes: (1) the lack of deep friendships at university, (2) the positive perceived impact of team sports on feelings of loneliness, and (3) the need for real connection in times of crisis. Thus, with regard to feelings of loneliness during the pandemic, being physically active seems to be small but potentially relevant factor among young individuals. The qualitative study suggests that first-year university students might buffer the lack of deep friendships and meaningful interactions by building social bonds in team sports. In times of physical distancing, young individuals vulnerable to loneliness may therefore require special support such as doing sports with physical distance and perceiving connected with their team for instance by digital devices and emotional coping.